Generalized dermonecrotic infection by Staphylococcus hyicus in a dog: Case report - Carvalho, Maria Priscila da Silva; Almeiada , Katherine Justino; Siqueira, Jackson de Oliveira; Souto, Flavio Jose; Silva, Mariana de França Oliveira da; Leite, Denny Parente de Sá Barreto Maia; Leite, Ana Greice Borba (Pubvet, 2024)
Infections caused by opportunistic bacteria are common in veterinary practice. Staphylococcus hyicus is the causative agent of exudative epidermitis in pigs, but it can also be isolated from the skin of healthy animals, affecting lactating piglets and after weaning. They are responsible for causing serious lesions in the integumentary tissue and can lead to systemic conditions in animals. Generalized dermonecrotic infection by Staphylococcus hyicus in dogs is a rare and difficult-to-treat condition. This study aims to report the case of a 9-year-old male, neutered Shetland Sheepdog, presenting severe edema in the left pelvic limb, lameness and progressive dermonecrotic lesions. The dog had had previous contact with pigs and the diagnosis was confirmed by bacterial culture and antibiogram. Despite antimicrobial and analgesic therapy, the clinical condition worsened, with progression to hypotension, tachycardia, tachypnea, and purulent secretion. The patient went into cardiorespiratory arrest and died. This case highlights the severity of this infection and the need for constant monitoring, early diagnosis, and appropriate treatment to minimize the risk of fatal outcomes.
Keywords: Antimicrobial resistance bacteria; dogs; pathogens; pyodermatitis